Justice: An Epistolary Essay. Issue 1 (2nd January 2017) - Barkan, Joshua; Pulido, Laura
Abstract : This exchange of letters considers the relationship between geography and different formulations of justice. On one hand, social movements have made visible the particular geographies of racialized, gendered, and class-based injustice. For this reason, the discipline of geography can be useful for social justice activists making justice claims. On the other hand, the public and private institutions to which justice claims are addressed often treat justice as a stable "thing" that can be achieved through protocols and procedures. Moreover, these institutionalized approaches to justice often limit justice claims, at times even enabling the unjust actions that initiated struggles for justice in the first place. Inasmuch as geographic knowledge is incorporated into this disciplining of justice, it, too, potentially limits social struggles. By considering this tension, we highlight the tremendous need for justice and the poverty of our institutionalized responses to that need.